The complete chloroplast genome of Tetraselmis desikacharyi (Chlorodendrophyceae) and phylogenetic analysis. Issue 1 (2nd January 2019) - Li, Linzhou; Li, Haoyuan; Kumar Sahu, Sunil; Xu, Yan; Wang, Hongli; Liang, Hongping; Wang, Sibo
Abstract: Tetraselmis desikacharyi is a marine alga, known as an important plankton for aquaculture as a feed organism. However, the genomic study on this class is rare. Here, we present a complete chloroplast genome of T. desikacharyi, belonging to Chlorodendrophyceae with a full length of 149, 934 bp, characterized by a very small single-copy (SSC) region without any genes and a large inverted repeat (IR) region. A maximum-likelihood (ML) phylogenetic analysis was performed using three kinds of data comprising 50 protein-coding genes, which placed the Chlorodendrophyceae as a deep-diverging lineage of the core Chlorophyta.